Morbidity and mortality associated with injuries: results of the Global Burden of Disease study in Brazil, 2008 - Mônica Rodrigues Campos; Vanessa dos Reis von Doellinger; Luiz Villarinho Pereira Mendes; Maria de Fatima dos Santos Costa; Thiago Góes Pimentel; Joyce Mendes de Andrade Schramm (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
The aim of this study was to estimate the global burden of disease from external causes in 2008 in Brazil, based on DALYs (disability-adjusted life years). YLLs (years of life lost) were estimated according to the method proposed by Murray & Lopez (1996). Meanwhile, the method for estimating YLDs (years lived with disability) included methodological adjustments taking the Brazilian reality into account. The study showed a total of 195 DALYs per 100 thousand inhabitants, of which 19 DALYs were related to external causes. Among YLLs, 48% were from unintentional causes and 52% from intentional causes. Among YLDs, unintentional causes predominated, with 95%. The share of YLLs in DALYs was 90%. The cause with the highest proportion of YLLs was "homicide and violence" (43%), followed by "road traffic accidents" (31%). Falls accounted for the highest share of YLDs (36%). The sex ratio (male-to-female) was 4.8 for DALYs, and the predominant age bracket was 15-29 years. Since external causes are avoidable, the study provides potentially useful information for policymakers in public security and health.